PENGARUH GAYA KEPEMIMPINAN, KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI (Studi Pada Kantor Kecamatan Lenteng Kabupaten Sumenep) - jurnalmap map; Moh. Haris; Nugroho Mawardi Wibowo; Muninghar ÔÇì (MAP (Jurnal Manajemen dan Administrasi Publik), 2019)
ABSTRACT This research was conducted at the Lenteng District Office in Sumenep Regency. with a total sample of 34 employees. Analysis of data using SPSS, this type of research is explanatory research using quantitative research approaches. The results of the study show that: 1) Simultaneously, leadership style, job satisfaction and organizational commitment have a significant effect on employee performance, 2) Partially, leadership style, job satisfaction and organizational commitment have a significant effect on employee performance. Keywords: The influence of leadership stylesb, Job satisfaction, Organizational commitment and Performance of Employees.